Pemodelan Numerik Pembebanan Pipa Menggunakan Metode Interpolasi Linier - Satyanaga, Alfrendo (Jurnal Teknik Sipil, 2005)
The movement of pipe in sand and clay are presented, formulated and analyzed using a linear interpolation method within the framework of elastic perfectly plastic Mohr Coulomb criteria and a new two-mechanism- non-associative piecewise linear Drucker Prager formulation. The two mechanisms are found when the variation of shear strength due to mean effective stress is separated from that due to plastic deviatoric strain. The modelling framework is intended to show the deformation and displacement of soil surrounding pipe. Furthermore it also describes the relationship between displacement and the force. Horizontal and vertical displacement are applied into pipe and they are modelled using finite element program, CRISP version 4. Slip element (interface) is attached in the vicinity of pipe to compare the deformation produced in this case with those without interface. Different material properties of cohesive and granular soil taken from laboratory tests are set in the model. All main parameters are recorded from lateral and horizontal loading test, as a part of the Collaborative Project on Soil/Pipe Interaction Mechanisms and Modelling. Application of the approach are presented and discussed with emphasis on identifying and optimizing some of the important factors that control the displacement of soil because of the movement of pipe. Several conclusions are drawn regarding the difficulties encountered in the numerical implementation. Illustrative numerical results for common geotechnical experiments on clay and sand using finite element software demonstrate the stable derivation of the two linear non associative Drucker Prager model.